SENGKETA USAHA PERTAMBANGAN DI WILAYAH HUTAN ELANG DODO KABUPATEN SUMBAWA - IWAN HARIANTO (University of Udayana, 2013)
West Nusa Tenggara, one of the regions rich in minerals mining. One of the mining companies doing business in the region is PT. Newmont. In 2003 the company was exploring the forest areas Elang Dodo Sumbawa. The presence of PT. Newmont in the region are not well received by the villagers of Lebangkar, resulting in rejection of the action in 2004 by way of demonstration and boycott the company's activities. Of the incident raises some issues: (1) who is the subject and what the object of the dispute? (2) how the process and the factors that cause disputes? (3) how the settlement of the dispute? The research method used in this research is an empirical law is derived from the analytical descriptik field data and data library. Processing and data analysis conducted qualitatively. Discussion until the conclusion in this paper can be described as follows: (1) subject to the dispute that is the village of Lebangkar with PT. Newmont and the Government of Sumbawa. The subject of dispute in the form of contract work necking VI results in 2005 with an area of ??87,500 ha. (2) The process of dispute which originated from exploration PT. Newmont in the woods Elang Dodo conducted in 2003. This exploration spawned several factors contributing to the dispute; violation of customs, reduced sources of income, lack of socialization, and control of natural resources. (3) dispute settlement efforts, through litigation and non-litigation. Settlement was not effective due; substance law, legal culture and legal structure.